2018
DOI: 10.1016/j.tjog.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oxytocin level, glucose metabolism components and cutoff values for oxytocin and anti-mullerian hormone in infertile PCOS women

Abstract: The mean oxytocin level in the PCOS infertile women was lower than non-PCOS women. Oxytocin showed a significant reverse correlation with AMH and HOMA-IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Which may be due to the reason that OT control metabolism and body weight by increasing energy expenditure, lipolysis and its effects on multiple homeostatic and neurobehavioral pathway [ 72 ]. In consistent with this study, [73] have reported that OT level was lower in the PCOS group in comparison to control and systemic administration of OT results ovary volume reduction, BW reduction and balance hormonal profile in women affected by PCOS. Therefore, it is evident that there had been decrease in the gonadal weight in the female treated with OT up to 90 days.…”
Section: Discussionsupporting
confidence: 89%
“…Which may be due to the reason that OT control metabolism and body weight by increasing energy expenditure, lipolysis and its effects on multiple homeostatic and neurobehavioral pathway [ 72 ]. In consistent with this study, [73] have reported that OT level was lower in the PCOS group in comparison to control and systemic administration of OT results ovary volume reduction, BW reduction and balance hormonal profile in women affected by PCOS. Therefore, it is evident that there had been decrease in the gonadal weight in the female treated with OT up to 90 days.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study revealed that oxytocin showed negative correlation with FI and HOMA in obese women with polycystic ovary syndrome [31]. Another study showed that oxytocin concentration correlated negatively with glycated haemoglobin (HbA 1c ) and FPG in diabetic metabolic syndrome patients [32].…”
Section: Original Papermentioning
confidence: 98%
“…The dysfunction in these women is characterized by the arrest of follicle maturation and the disturbed selection of the dominant follicle, and an increased number of early antral follicles [44]. PCOS is often associated with obesity (38-66% PCOS patients), insulin resistance (IR), and decreased pregnancy rates in natural and assisted conception cycles [46]. However, it is debatable if IR is the consequence of PCOS or obesity itself [46].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…PCOS is often associated with obesity (38-66% PCOS patients), insulin resistance (IR), and decreased pregnancy rates in natural and assisted conception cycles [46]. However, it is debatable if IR is the consequence of PCOS or obesity itself [46]. Ovarian aging and age at menopause could be delayed in women with PCOS [44].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%